DEMONSTRASI BENDA KONKRIT DALAM PEMBELAJARAN MATEMATIKA - Suparni Suparni (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2015)
Mathematicts is an important subject at Elementary Schools. Preliminary observation at many Elemmentary School indicated that student’s mathematic achievement was not satisfactory. The student’s understanding of number operations was olso low. One of many ways to improve the student’s activities and mathematic achievement is through the use of block Dienes in teaching number operations.